Capacity Building and Districts' Decision to Implement Coaching Initiatives - Melinda M. Mangin (Arizona State University, 2014)
The United States has experienced tremendous growth in the development of coaching initiatives including professional training programs, state endorsements and resources for coaches. These developments bring attention to the potential for coaching to improve education. They also raise the question of how best to facilitate implementation in local districts. One approach is to build capacity for coaching in schools and districts. Capacity building, as a policy tool, can facilitate the skills and knowledge necessary to engage in new practices. To understand the influence of capacity building efforts on districts' decision to implement coach initiatives, this study examines how one Regional School District (RSD) worked to build capacity for literacy coaching among its 20 constituent districts. Data were collected through annual interviews with administrators in all 20 districts over three years. To analyze the data, I employed Weiss' decisionmaking framework, which examines the influence of ideology, interests and information on policy positions and decision outcomes (1983). Findings suggest that the RSD's ongoing capacity building efforts influenced districts' decision to implement coach roles, even in districts that initially expressed no interest in coaching. This study provides insights into the utility of capacity building for implementing coach roles and into the "politics" behind coaching initiatives.